2015
DOI: 10.3390/molecules201018237
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening Reactions through C-O Bond Cleavage Uniquely Adding Chemical Functionality to Boron Subphthalocyanine

Abstract: Abstract:We are reporting the unexpected reaction between bromo-boron subphthalocyanine (Br-BsubPc) and THF, 1,4-dioxane or γ-butyrolactone that results in the ring opening of the solvent and its addition into the BsubPc moiety. Under heating, the endocyclic C-O bond of the solvent is cleaved and the corresponding bromoalkoxy-BsubPc derivative is obtained. These novel alkoxy-BsubPc derivatives have remaining alkyl-bromides suitable for further functionalization. The alkoxy-BsubPcs maintain the characteristic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…The 1 H NMR spectrum of 6 features four CH 2 peaks centered at δ = 2.19, 1.53, 0.67, and 0.42 ppm, together with a singlet at δ = −0.04 ppm with intensity integration of 18 protons, in accordance with a −N(TMS) 2 group (Figure S14). Bender et al 8 reported the formation of small amounts (15%) of (subPc)BO(CH 2 ) 4 Br upon refluxing a THF solution of (subPc)BBr in the presence of a Grignard reagent, in parallel with our observation.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The 1 H NMR spectrum of 6 features four CH 2 peaks centered at δ = 2.19, 1.53, 0.67, and 0.42 ppm, together with a singlet at δ = −0.04 ppm with intensity integration of 18 protons, in accordance with a −N(TMS) 2 group (Figure S14). Bender et al 8 reported the formation of small amounts (15%) of (subPc)BO(CH 2 ) 4 Br upon refluxing a THF solution of (subPc)BBr in the presence of a Grignard reagent, in parallel with our observation.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…Organozinc as well as organosilicon reagents have been used as mild reagents to introduce carbon ligands to the subphthalocyanine or sub­porphyrin boron complexes, which might be regarded as examples of carbon–element bond activations. Recently, Bender et al reported the ring opening of various cyclic ethers and esters in the presence of (subPc)­BBr . It is also notable that a related subporphyrin boron hydride complex has recently been reported to act as a mild hydride donor, and that a subporphyrin boron hydroperoxide has been shown to exhibit weak oxidizing ability …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The cleavage of endocyclic C-O bonds has been reported for boron based Lewis acids 57,58 as well as for non-electron-decient boron subphthalocyanine, proposing the formation of a fourmembered ring intermediate and subsequent s-bond metathesis. 59,60 Therefore we tested the reactivity of the boranes DAB R -Br towards thf in the absence of any cluster species. Indeed, NMR investigations ( 1 H, 11 ] cluster core can be best described as a tricapped trigonal prism with three different prims heights and C S symmetry.…”
Section: Ring-opening Of Tetrahydrofuranmentioning
confidence: 99%
“…1 They are used as synthons in the synthesis of A3B phthalocyanines, and also in various photonic processes, such as photovoltaics, 2 and optical imaging. 3 The chemistry of this domed structure has been explored obviously on the ring opening chemistry front, 4 but also on the apical substitution at the Boron atom. 5 Reaction with an acid is also of interest: it may drastically affect both the reactivity and the optical properties of the macrocycle.…”
mentioning
confidence: 99%